2010
DOI: 10.1117/1.3463003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling light propagation through bacterial colonies and its correlation with forward scattering patterns

Abstract: Abstract. Bacterial colonies play an important role in the isolation and identification of bacterial species, and plating on a petri dish is still regarded as the gold standard for confirming the cause of an outbreak situation. A bacterial colony consists of millions of densely packed individual bacteria along with matrices such as extracellular materials. When a laser is directed through a colony, complicated structures encode their characteristic signatures, which results in unique forward scattering pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Subsequently, scalar diffraction theory was used to predict the forward scattering pattern generated by the colony. The coordinate system was defined in Figure 4a and the colony was treated as an optical phase F'(x a ,y a ) and amplitude t(x a ,y a ) modulator with the fitted Gaussian crosssection as below (Bae et al, 2007(Bae et al, , 2008(Bae et al, , 2010:…”
Section: Theoretical Modeling Of Scattering From Microcolonymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, scalar diffraction theory was used to predict the forward scattering pattern generated by the colony. The coordinate system was defined in Figure 4a and the colony was treated as an optical phase F'(x a ,y a ) and amplitude t(x a ,y a ) modulator with the fitted Gaussian crosssection as below (Bae et al, 2007(Bae et al, , 2008(Bae et al, , 2010:…”
Section: Theoretical Modeling Of Scattering From Microcolonymentioning
confidence: 99%
“…Since Wyatt (Wyatt, 1969), light scattering has been widely used to provide fast, accurate, and non-disruptive interrogation of biological samples (Bronk et al, 1992(Bronk et al, , 2001Jones et al, 1998;Kottmeier et al, 2009;Samorski et al, 2005). While these examples mostly dealt with cells in liquid state, our group introduced a new concept of using laser to interrogate the bacterial colonies to generate unique scattering patterns which worked as an individual ''fingerprint'' for each bacterial kind (Bae et al, 2007(Bae et al, , 2010. This technology provided label-free, fast, and reliable identification of bacterial species via comparing the scattering patterns with the previously recorded image database.…”
Section: Introductionmentioning
confidence: 99%
“…In their study it was observed that Bacillus colony under extreme air-drying condition (7% agar) grew more vertically compared to less drying condition (1% agar), where colony grew more laterally. Such variation in colony profile will impart immense difference in BARDOT scatter patterns based on physical theoretical variations of light forward scattering as mentioned in our previous studies [18,27]. This may be the reason for the irreproducible and incongruent scatter patterns under extreme drying condition, when compared to short drying condition.…”
Section: Extreme Air-drying Conditionsmentioning
confidence: 95%
“…A detailed model of the bacterial colony is given in Bae et al (2007Bae et al ( , 2010 where the characterizing parameters of the scattering patterns are correlated to the colony height and diameter. From the model it appears clear how the scattering angle undergoes to significant variations when either the thickness or the diameter of the colony changes.…”
Section: Scattering Angle and Camera Distance Adjustingmentioning
confidence: 99%